Route optimization of feeder bus for Electric Train Service - Kwong, A.C.K. (IEEE Computer Society, 2014)
The Electric Train Service (ETS), which connects the cities of Kuala Lumpur and Ipoh, has been in operation since 2010. The ETS has not only provided a safe, fast and cost effective way to travel between these two cities, but has also spurred the economic activities of the major towns between them. However, the lack of an effective feeder bus system that brings commuters to the ETS stations remains a significant problem. The objective of this paper is to design a wide coverage feeder bus route that is also effective and efficient in terms of service. Specifically, genetic algorithm has been used to optimize the feeder bus route. The optimization is performed to attain the widest service coverage, lowest operation cost, shortest total travel time, shortest total travel distance and to meet the highest demand. As a test case, the Batu Gajah, Perak ETS station has been used. Simulation results show that solving the route optimization problem can produce a wide coverage route with high effectiveness and efficiency in service. Â© 2014 IEEE.